Об экспоненциальной устойчивости нейронной сети Хопфилда на временной шкале - Лукьянова, Т.А. (Доповіді НАН України, 2011)
Отримано достатні умови рівномірної експоненціальної стійкості в цілому стану рівноваги нейронної системи на часовій шкалі. Ефективність отриманих достатніх умов проілюстровано на прикладі. We present new stability results of neural systems on the time scale. The sufficient conditions of exponential stability are given. The efficiency of the obtained sufficient conditions is tested by a numerical example.